Dopamine in Fear Extinction - Salinas-Hernández, Ximena I.; Duvarci, Sevil (Frontiers in Synaptic Neuroscience, 2021)
The ability to extinguish fear memories when threats are no longer present is critical for adaptive behavior. Fear extinction represents a new learning process that eventually leads to the formation of extinction memories. Understanding the neural basis of fear extinction has considerable clinical significance as deficits in extinction learning are the hallmark of human anxiety disorders. In recent years, the dopamine (DA) system has emerged as one of the key regulators of fear extinction. In this review article, we highlight recent advances that have demonstrated the crucial role DA plays in mediating different phases of fear extinction. Emerging concepts and outstanding questions for future research are also discussed.